Oral History in South Africa: Autoethnography, Methodologies and Ethics - Sekgothe Mokgoatšana; Christina Landman; Stewart L. Kugara; Pfarelo E. Matshidze; Munyaradzi Mushonga; Motlatsi Thabane; Radikobo Ntsimane; Chitja Twala; Kogielam K. Archary; John R. Phori (AOSIS, 2025)
Colonial and apartheid-era historical narratives in South Africa often disregard oral testimonies, leaving significant gaps in understanding the country's rich and complex past. This scholarly book explores the methodologies and ethics of oral history to address these omissions and to elevate oral testimonies as vital tools in historical scholarship. This book brings together ten chapters authored by leading academics and researchers. It critically examines how oral history methodologies can be contextualised within South Africa's diverse and multifaceted society. Rather than focusing on Eurocentric approaches, it emphasises the need to rethink the ethics and practices of oral history from an Afrocentric perspective. Through its transdisciplinary and interdisciplinary lens – spanning history, indigenous knowledge studies, museum and archival studies, and folklore – this book advocates for the recognition of interviewees as knowledge holders, fostering meaningful exchanges rather than mere knowledge extraction. The authors emphasise the need to protect and expand oral history archives, ensuring the representation of marginalised voices and redressing past injustices. With original research, this volume sheds light on the transformative potential of oral history in South Africa, offering new arguments and perspectives. It aims to inspire scholars, researchers, and specialists to rethink conventional practices and to bridge the divide between written and oral histories. This is essential literature for scholars and practitioners in history, oral history, theology, museum studies, and related fields, as it reimagines the role of oral testimonies in producing inclusive and credible historical narratives.